Design and Implementation of the Natural Light Reproduction System Based on Context Awareness in WSN - Yun-Joo Kim; Sook-Youn Kwon; Jae-Hyun Lim (International Journal of Distributed Sensor Networks)
Changes in natural light in the daily cycle and monthly cycle and its seasonal changes create rhythms in bodies of living creatures including humans. The circadian rhythm connected to natural light stimulates psychological states and hormonal changes. As such, natural light is a major environmental factor that affects humans' psychological and physiological conditions. To create healthy and comfortable lighting environments in windowless space such as a basement where no natural light can enter, the daily, monthly, and seasonal cycles of natural light need to be represented by means of artificial lightings. Upon certain situations related to purposes of space and user behaviors, lighting control technology is required for appropriate lighting environments. To this end, this study designs and implements a natural light reproduction system based on context awareness in wireless sensor networks to restructure lighting environments in adaptation to the changing situation of the occupant. As the object space in the experiment, a clothing shop to occupy the largest portion of underground space was selected. The scenarios were selected for each time period in connection with the behaviors of the seller who resided there for a long time. The suggested system's performance was evaluated in terms of conformity with natural light, comfort, and energy-saving effect.